2015
DOI: 10.1051/0004-6361/201526556
|View full text |Cite
|
Sign up to set email alerts
|

12CO emission from EP Aquarii: Another example of an axi-symmetric AGB wind?

Abstract: The CO(1−0) and (2−1) emission of the circumstellar envelope of the asymptotic giant branch (AGB) star EP Aqr has been observed in 2003 using the IRAM Plateau-de-Bure Interferometer and in 2004 with the IRAM 30-m telescope at Pico Veleta. The line profiles reveal the presence of two distinct components centred on the star velocity, a broad component extending up to ∼10 km s −1 and a narrow component indicating an expansion velocity of only ∼2 km s −1 . An early analysis of these data was performed under the as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 13 publications
9
29
0
Order By: Relevance
“…It gives evidence for a strong polar enhancement, at variance with a weak radial dependence up to r ∼ 8 ′′ . It provides a unified picture of the two models that have been proposed earlier, the model of Winters et al (2007) corresponding to V rad dependent on r but independent on α, that of Nhung et al (2015b) corresponding to V rad dependent on α but independent on r. The projections of the V rad distributions on the sin α and r axes illustrate the preference for the latter over the former.…”
Section: Application To Real Observationsmentioning
confidence: 64%
See 1 more Smart Citation
“…It gives evidence for a strong polar enhancement, at variance with a weak radial dependence up to r ∼ 8 ′′ . It provides a unified picture of the two models that have been proposed earlier, the model of Winters et al (2007) corresponding to V rad dependent on r but independent on α, that of Nhung et al (2015b) corresponding to V rad dependent on α but independent on r. The projections of the V rad distributions on the sin α and r axes illustrate the preference for the latter over the former.…”
Section: Application To Real Observationsmentioning
confidence: 64%
“…The R-dependence is steeper for CO(2-1) than for CO(1-0) as expected, with respective power indices −1.2 and −0.9. The sky maps of the mean Doppler velocity display a small north-west/south-east asymmetry, interpreted by Nhung et al (2015b) as resulting from the small inclination of the star axis on the line of sight. In the θ = 0 approximation the stellar longitude ω is equal to the sky position angle ϕ of the pixel and the stellar latitude α is related to x by the relation x = R tan α.…”
Section: Application To Real Observationsmentioning
confidence: 96%
“…Spatially resolved observations obtained at IRAM (Winters et al 2003;Nhung et al 2015a) on EP Aqr, and on other sources such as RS Cnc (Libert et al 2010;Hoai et al 2014;Nhung et al 2015b) and X Her (Kahane & Jura 1996) are generally interpreted as the superposition of a slowly expanding wind with a bipolar outflow. The presence of irregularities in the morpho-kinematics has been interpreted as suggesting an episode of increased mass loss rate (Knapp et al 1998;Nakashima 2006;Winters et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarises its properties. There have been several recent investigations of the CSE around EP Aqr (Nhung et al 2015;Homan et al 2018;Tuyet Nhung et al 2019;Hoai et al 2019;Tuan-Anh et al 2019), most of them of the CO lines with ALMA. Tuan-Anh et al (2019) found jets extending from 25 to 1000 au.…”
Section: Properties Of Ep Aqrmentioning
confidence: 99%